Integrating slow food knowledge and traditional food practices into educational curricula: Implications to social environment conservation - Fazal Manan; Dolly Priatna; Shujaul Mulk Khan; Shakil Ahmad Zeb; Abdullah; Hamid Masood; Imran Ali; Gulnar Kairzhanovna Tulindinova; Bibi Gul Zhumabekova; Syahik Nurbani (Universitas Pakuan, 2026)
Slow Food is increasingly recognized as essential for human health and quality of life because it promotes the consumption of fresh, natural, organic, and locally produced foods that are free from synthetic inputs and richer in nutritional value. Beyond health benefits, the Slow Food movement also contributes to environmental conservation by reducing carbon emissions, supporting sustainable agriculture, and preserving local food systems. This study employed a qualitative integrative review methodology to examine how Slow Food knowledge and traditional culinary practices can be integrated into educational curricula. The research framework consisted of three main phases: systematic literature selection, thematic analysis, and synthesis of findings. This study is distinctive in its integrative approach, which connects Slow Food principles, traditional food practices, and curriculum development. The findings highlight the role of both formal and informal education as transformative platforms for promoting sustainable agricultural systems, preserving cultural heritage, and fostering social and environmental responsibility. Education supports the production of slow, clean, and organic food by increasing awareness and encouraging sustainable food growing practices. Through education, students gain knowledge and practical skills to cultivate vegetables and develop school or community gardens. Educational institutions act as key agents in knowledge development, advocacy, research, and the promotion of sustainable Slow Food practices. They contribute through curriculum integration, schoolyard gardening initiatives, community engagement, and policy advocacy. Higher education institutions, particularly universities, can embed Slow Food education into multidisciplinary curricula, equipping students to address contemporary food system challenges, promote global citizenship, and participate in slow, clean, and fair food.